Potassium‐induced cortical spreading depression bilaterally suppresses the electroencephalogram but only ipsilaterally affects red blood cell velocity in intraparenchymal capillaries. Issue 4 (18th January 2013) - Unekawa, Miyuki; Tomita, Yutaka; Toriumi, Haruki; Masamoto, Kazuto; Kanno, Iwao; Suzuki, Norihiro
Abstract Cortical spreading depression (CSD) is a repetitive, propagating profile of mass depolarization of neuronal and glial cells, followed by sustained suppression of spontaneous neuronal activity. We have reported a long‐lasting suppressive effect on red blood cell (RBC) velocities in intraparenchymal capillaries. Here, to test the hypothesis that the prolonged decrease of RBC velocity in capillaries is due to suppression of neuronal activity, we measured CSD‐elicited changes in the electroencephalogram (EEG) as an index of neuronal activity. In isoflurane‐anesthetized rats, DC potential, EEG, partial pressure of oxygen (PO2), and cerebral blood flow (CBF) were simultaneously recorded in the temporo‐parietal region. The velocities of fluorescently labeled RBCs were evaluated by high‐speed camera laser scanning confocal fluorescence microscopy with our original software, KEIO‐IS2. Transient deflection of DC potential and PO2 and increase of CBF were repeatedly detected only in the ipsilateral hemisphere following topical KCl application. On the other hand, the relative spectral power of EEG was reduced bilaterally, showing the lowest value at 5 min after KCl application, when the other parameters had already returned to the baseline after the passage of CSD. Mean RBC velocity in capillaries was slightly but significantly reduced during and after passage of CSD in the ipsilateral hemisphere but did not change in the contralateral hemisphere in the same rats. We suggest that mass depolarization of neuronal and glial cells might transiently decelerate RBCs in nearby capillaries, but the sustained reduction of ipsilateral RBC velocity might be a result of the prolonged effect of CSD, not of neuronal suppression alone. © 2013 Wiley Periodicals, Inc.